PREVENTION OF DRY EYE SYNDROME IN WOMEN OF MENOPAUSAL AGE (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Dry eye syndrome is a common condition in menopausal women, primarily due to hormonal changes that affect tear production and ocular surface stability. This article aims to explore the mechanisms behind the development of dry eye syndrome during menopause, identify risk factors, and discuss effective prevention strategies. A combination of hormonal influence, environmental factors, systemic diseases, and lifestyle contribute to its progression. Early identification and prevention are key to maintaining quality of life and ocular health in menopausal women.